Odpowiedź :
[tex]10)\\\\a)\\\\\frac{1}{3}x-2=x+2\ \ |*3\\\\x-6=3x+6\\\\x-3x=6+6\\\\-2x=12\ \ |:(2)\\\\x=-6\\\\b)\\\\1-\frac{6}{7}x=\frac{4}{7}\ \ |*7\\\\7-6x=4\\\\-6x=4-7\\\\-6x=-3\ \ |:(-6)\\\\x=\frac{3}{6}=\frac{1}{2}[/tex]
[tex]c)\\\\6(\frac{1}{4}x-2)=18\\\\\frac{3}{2}x-12=18\\\\\frac{3}{2}x=18+12\\\\\frac{3}{2}x=30\ \ |*(\frac{2}{3})\\\\x=20[/tex]
[tex]12)\\\\ a)\\\\ \frac{x}{3}+1= \frac{5}{6}+ \frac{x}{2}\ \ |*6\\\\2x+6=5+3x\\\\2x-3x=5-6\\\\-x=-1\ \ |*(-1)\\\\x=1\\\\d)\\\\\frac{2x+3}{5}=\frac{2-x}{3} +x\ \ |*15\\\\3(2x+3)=5(2-x)+15x\\\\6x+9=10-5x+15x\\\\6x+5x-15x=10-9\\\\-4x=1\ \ |:(-4)\\\\x=-\frac{1}{4}[/tex]
[tex]e)\\\\\frac{ 3x-5 }{2}-\frac{ 5x-1 }{10}=0\ \ |*10\\\\5(3x-5)-(5x-1)=0\\\\15x-25-5x+1=0\\\\10x-24=0\\\\10x=24\ \ |:10\\\\x=\frac{24}{10}=\frac{12}{5}=2\frac{2}{5}[/tex]
[tex]f)\\\\ \frac{x}{2}= \frac{2}{5}(4-x)-4\ \ |*10\\\\5x=4(4-x)-40\\\\5x=16-4x-40\\\\5x+4x=-24\\\\9x=-24\ \ |:9\\\\x=-\frac{24}{9}=-\frac{8}{3}=-2\frac{2}{3}[/tex]